Development of a Universal Microarray Based on the Ligation Detection Reaction and 16S rRNA Gene Polymorphism To Target Diversity of Cyanobacteria - Castiglioni, Bianca (American Society for Microbiology, 2004)
The cyanobacteria are photosynthetic prokaryotes of significant ecological and biotechnological interest, since they strongly contribute to primary production and are a rich source of bioactive compounds. In eutrophic fresh and brackish waters, their mass occurrences (water blooms) are often toxic and constitute a high potential risk for human health. Therefore, rapid and reliable identification of cyanobacterial species in complex environmental samples is important. Here we describe the development and validation of a microarray for the identification of cyanobacteria in aquatic environments. Our approach is based on the use of a ligation detection reaction coupled to a universal array. Probes were designed for detecting 19 cyanobacterial groups including Anabaena/Aphanizomenon, Calothrix, Cylindrospermopsis, Cylindrospermum, Gloeothece, halotolerants, Leptolyngbya, Palau Lyngbya, Microcystis, Nodularia, Nostoc, Planktothrix, Antarctic Phormidium, Prochlorococcus, Spirulina, Synechococcus, Synechocystis, Trichodesmium, and Woronichinia. These groups were identified based on an alignment of over 300 cyanobacterial 16S rRNA sequences. For validation of the microarrays, 95 samples (24 axenic strains from culture collections, 27 isolated strains, and 44 cloned fragments recovered from environmental samples) were tested. The results demonstrated a high discriminative power and sensitivity to 1 fmol of the PCR-amplified 16S rRNA gene. Accurate identification of target strains was also achieved with unbalanced mixes of PCR amplicons from different cyanobacteria and an environmental sample. Our universal array method shows great potential for rapid and reliable identification of cyanobacteria. It can be easily adapted to future development and could thus be applied both in research and environmental monitoring.